MONITORING OF FLANK WEAR AND DAMAGE ON TURNING CUTTING TOOLS BY IMAGE PROCESSING - Joseph Kalil Khoury Junior; John Kenneth Schueller; Francisco de Assis Carvalho Pinto; Geice Paula Villibor (The Journal of Engineering and Exact Sciences)
The development of the tool wear monitoring system by machining processes has been well recognized in the machine industry mainly due to the growing demand for product quality and improved productivity. For this, artificial vision systems have been used as a measurement tool in various application areas. Thus, the objective was to develop a system automatic based in the image processing to identify and measure flank wear in machining tool. Image processing techniques, discriminant function, to identify insert breakage, and Hough Transform, to find the flank wear profile, achieved over accuracy. Consequently, 94.3% to identify between worn and broken insert and 0.04 mm mistake in measurement of flank wear width compared with microscope.